Clinical characteristics and outcomes of anti-MDA5 dermatomyositis: a retrospective study - Tulaton Sodsri; Tananchai Petnak; Thitiporn Suwatanapongched; Chayanin Nitiwarangkul; Nantakarn Pongtarakulpanit; Pintip Ngamjanyaporn (BMC Rheumatology)
Abstract Background Anti-MDA5 dermatomyositis (anti-MDA5 DM) is a rare but severe subtype of dermatomyositis associated with high mortality. This study aimed to describe clinical characteristics and identify variables associated with rapidly progressive interstitial lung disease (RP-ILD) and mortality among affected patients. Methods Patients diagnosed with anti-MDA5 DM between January 2013 and October 2022 were included. Demographics, clinical manifestations, and laboratory data were collected. Univariable Cox proportional hazard regression was used to assess mortality predictors, while logistic regression models identified factors associated with RP-ILD. Results Among 26 patients (mean age, 56.6 ± 15.1 years, 7 men), the most common clinical manifestation was Gottrón’s papules (80.8%), followed by ILD (73.1%), periungual erythema (69.2%), heliotrope rash (61.5%), V-sign (42.3%), arthritis (42.3%), weakness (38.5%), shawl sign (34.6%), mechanic’s hand (34.6%), and Raynaud’s phenomenon (19.2%). Among 19 ILD patients, 9 (47.4%) developed RP-ILD, and seven patients died over a median follow-up of 1.5 years. The overall mortality rate in this cohort was 26.9%, with 77.8% having RP-ILD. Mortality was associated with male sex (HR, 7.7; 95% CI, 1.49–39.9; P = 0.02) and RP-ILD, which had a risk difference of 77.8 (95% CI 50.6-104.9%; P = 0.001). Arthritis (P = 0.01) and ANA positivity (P = 0.03) were associated with reduced risk of RP-ILD. Patients with RP-ILD tended to receive aggressive treatments, including triple therapy regimens (55.6%), which consisted of a combination of intravenous methylprednisolone and intravenous cyclophosphamide with either rituximab or a calcineurin inhibitor. Additional treatments included intravenous immunoglobulin (22.2%) and plasma exchange (33.3%). Conclusion Anti-MDA5 DM was associated with a high prevalence of ILD, particularly RP-ILD, contributing to increased mortality, underscoring the need for early identification of high-risk patients and personalized management. Take-home message Male sex was a key predictor of RP-ILD and poor prognosis in anti-MDA5 dermatomyositis patients. Conversely, arthritis and ANA positivity might be associated with a lower risk of RP-ILD. Clinical trial number Not applicable.